Review of the Development of Low Earth Orbit Satellite Communication for Smart High-Speed Railway - Zhaoyang SU; Liu LIU; Jiachi ZHANG; Tao ZHOU; Wei LIN; Yiqun LIANG (天地一体化信息网络)
Low-earth orbit satellites have the advantages of wide bandwidth, low latency, and large coverage, making them very suitable as a supplement to ground cellular networks.Low-earth orbit satellites can meet the requirements of smart high-speed railway full line coverage and seamless connection, which helps to build an integrated communication network between ground and space.Considered the shortcomings of the current railway mobile communication network, the application and key technologies of low earth orbit satellites in smart high-speed railway were studied.Firstly, the communication requirements of smart high-speed railway were analyzed, and then the development status of railway satellite communication at home and abroad were introduced.Finally, the key technologies and challenges of low earth orbit satellite application in the field of smart high-speed rail were discussed from the aspects of propagation characteristics, physical layer parameters, beam handover, and resource management.